Mapping stakeholders along the climate information service value chain in Nigeria - Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2024)
Agriculture plays an important role in Nigeria’s development as it is a significant contributor to the country’s economy and the primary employer of its labour force. However, the sector is disproportionally affected by the impacts of climate change. Addressing climate change challenges in agriculture and food systems require transformative actions not only at individual farmer levels but also at the organisational or institutional and the systemic level. By providing relevant science-based climate information needed to understand, anticipate, and manage climate-related risks in agriculture planning, policy and practice across scales, climate information service (CIS) plays a central role in responding to climate change challenges. This report documents the outputs of the stakeholder mapping exercises conducted as part of the “Building Agricultural Systems Resilience through an Effective Early Warning System in Nigeria” (EWS) project activities. EWS aims to enhance operational capacity for key early warning actors, bolstering Nigeria’s agricultural resilience to climate change. The report identified and mapped the key stakeholders along the CIS value chain in agriculture and food systems in Nigeria. The mapping exercise also analysed the interactions among key stakeholders along the value chains. In total 31 stakeholder institutions and organizations working along the CIS value chain in Nigeria have been identified by the participants throughout the stakeholder engagement process. Most of the identified institutions worked in more than one segment of the value chain. NiMET is a key central actor along the CIS value chain in Nigeria, followed by NIHSA, and collaborate directly with all other actors in the ecosystems. Extension services, farmers-based organizations and private sector actors are important stakeholders contributing to the dissemination and use of CIS by farmers. Some of the identified institutions do not fall strictly in any of the segments of the CIS value chains but provide funding and technical support for the development CIS system and CIS dissemination to farmers. A public-partnership approach for CIS dissemination could strengthen the collaboration among key actors along the CIS value chain and improve the effectiveness of the CIS dissemination.